Beyond the Haze : Deciphering Cannabis from Epidemiology to Legislation (International Journal of Scientific Research in Science and Technology, 2024)
This thorough analysis explores the complex world of cannabis, looking at epidemiological patterns, international legal nuances, and its complex role in India. Global epidemiology examination provides insight into consumption trends and the resulting public health consequences. Moreover, a thorough examination of legal frameworks clarifies the various regulatory strategies used in various jurisdictions, with an emphasis on India’s changing legislative environment. Additionally, the paper carefully considers cannabis’s medicinal potential in addition to its short- and long-term adverse effects. The therapeutic spectrum and related dangers are clearly defined, ranging from reducing the symptoms of different medical illnesses to possible negative consequences. By synthesizing a wealth of knowledge spanning epidemiology, legal frameworks, and therapeutic considerations, this review provides valuable insights for legislators, healthcare professionals, and researchers navigating the complex terrain of cannabis.